Different environmental variables predict body and brain size evolution in Homo - Manuel Will (Nature Portfolio, 2021)
Increasing body and brain size constitutes a key pattern in human evolution, but the mechanisms driving these changes remain debated. Using a large fossil dataset combined with global paleoclimatic reconstructions, the authors show that different environmental variables influenced the evolution of brain and body size in Homo.